Sentimen Pengguna Twitter Mengenai Isu Kebocoran Data Dengan Algoritma Naïve Bayes - Achmad Musyaffa Taufiqi; Aryo Nugroho (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
Sensitive data leakage occurs when it is unintentionally made available to or accessed by unauthorized individuals. Sentiment analysis is the process of analyzing text to gather different data from the web and social media in order to obtain opinions from internet users on a particular topic. Sentiment analysis is a branch of Natural Language Processing (NLP) that develops a system for extracting and identifying public opinion from text that is then transformed into structured data. One kind of technique for classifying data is Naïve Bayes. Naïve Bayes uses conditional probabilities to assign labels to instances. This study collects information from tweets sent by Twitter users on the subject of